Bullies' Attitudes on Twitter: A Forensic Linguistics Analysis of Cyberbullying (Systemic Functional Linguistics Approach) - Nabila Putri Supriadi; Wawan Gunawan; R. Dian Dia-an Muniroh (Passage, 2020)
Cyberbullying has gained more concern among linguists and law enforcers due to its negative impacts on its victim. Aside from that, bullies can also face serious legal consequences. This study attempts to identify legal consequences of the cyberbullies’ language use as evidenced on Twitter by identifying the attitudinal systems used by the bullies. This followed a qualitative design involving categorizing data and examining the relationship between the categories. The data were 52 tweets, which consisted of bullying elements towards non-specific persons (students from an institution) from Twitter. The data were then categorized into Martin and White’s (2005) attitudinal system. The analysis found the languages of attitudes used by the bullies including 1) judgement (69%), 2) appreciation (18%), and 3) affect (13%). The findings of this study were discussed under the Laws of Information and Electronic Transaction, and viewed from forensic linguistic perspective.Keywords: Cyberbullying, Bullies, Twitter, Attitudes, Forensic Linguistics.